2006
DOI: 10.1177/039139880602900114
|View full text |Cite
|
Sign up to set email alerts
|

Our Nine-Year Experience with the Self-Locating Catheter: Comparison of Malfunction Rate with Other Tenckhoff Catheter Variants

Abstract: Objective To evaluate catheter-related complications among self-locating and other variants of Tenckhoff catheters. Patients and Methods We studied all self-locating catheters implanted in our hospitals from May/97 to Dec/05. We extended the follow-up to Jun/05. We collected demographic data, causes of catheter withdrawal and dropping of PD. We studied data about technique and catheter related complications. Results We included 328 catheters in 285 patients. There were 258 self-locating, 55 straight and 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 11 publications
0
12
1
1
Order By: Relevance
“…As prophylaxis for migration, catheters that are weighted or utilize a swan neck design can be used; studies suggest better long‐term results with these methods of treatment . Some authors recommend catheter placement with an additional suture from the inside of the peritoneum when catheter is inserted.…”
Section: Late Complicationsmentioning
confidence: 99%
“…As prophylaxis for migration, catheters that are weighted or utilize a swan neck design can be used; studies suggest better long‐term results with these methods of treatment . Some authors recommend catheter placement with an additional suture from the inside of the peritoneum when catheter is inserted.…”
Section: Late Complicationsmentioning
confidence: 99%
“…The weight of the tip (12 g) is intended to prevent catheter displacement when floating in the peritoneal fluid or as a result of bowel loop movement. Although the incidence of malfunction with SLCs is lower when compared to other types of catheters, (14,(16)(17)(18)(19)(20)(21)(22)(23), current prospective studies are limited and there is no record of randomized studies.…”
Section: ♦ Conclusionmentioning
confidence: 99%
“…Multiple studies have shown improved function, decreased migration, and longer catheter survival with the SLPDC. [9][10][11][12][13][14] However, drawbacks of the SLPDC include the signi cantly increased diameter of the terminal tungsten cylinder compared to the nominal diameter of the catheter precluding the ability to place it percutaneously through small sheaths, its inability to vary the length of the effective catheter, and its restricted application to a straight catheter instead of a coiled catheter.…”
Section: Discussionmentioning
confidence: 99%